2004
DOI: 10.1038/modpathol.3800158
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of tumor necrosis factor (TNF)α and TNFα receptor I in human viral myocarditis: clinicopathologic correlations

Abstract: Proinflammatory cytokines, including tumor necrosis factor (TNF)a, have been recognized as important physiopathogenetic factors in the initiation and continuation of inflammatory cardiomyopathies. Experimental and preliminary human studies have demonstrated that TNFa plays a crucial role in enteroviral-induced myocarditis. In this study, we investigated the expression of TNFa and both its receptors (TNFRI and TNFRII) in both viral and nonviral myocarditis. Myocardial expression of TNFa was then correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 49 publications
(50 reference statements)
4
47
0
2
Order By: Relevance
“…For example, patients with infectious and viral myocarditis have elevated levels of TNF-␣ protein and mRNA in myocardial tissue. [32][33][34] TNF-␣ plays a major role in the progression of myocarditis, given that targeted myocardial overexpression of TNF-␣ leads to severe myocarditis, cardiomegaly, and progressive myocardial fibrosis. [35][36][37] In addition, exogenously administered TNF-␣ increases myocarditis, and inhibition of TNF-␣ with antibodies or soluble receptors attenuates viral myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with infectious and viral myocarditis have elevated levels of TNF-␣ protein and mRNA in myocardial tissue. [32][33][34] TNF-␣ plays a major role in the progression of myocarditis, given that targeted myocardial overexpression of TNF-␣ leads to severe myocarditis, cardiomegaly, and progressive myocardial fibrosis. [35][36][37] In addition, exogenously administered TNF-␣ increases myocarditis, and inhibition of TNF-␣ with antibodies or soluble receptors attenuates viral myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…25,28 The causative relationship between HCV infection and dilated cardiomyopathy remains ambiguous; increased tumor necrosis factor (TNF) and cytokine expression have been implicated. 29 Bowles et al 24 conducted a multicenter study of 624 patients with biopsy-proven myocarditis (66%) or borderline myocarditis (34%). Evidence of viral genome (adenovirus, enterovirus, and cytomegalovirus in decreasing frequency) was identified in 239 (38%) of subjects' endomyocardial biopsies.…”
Section: Etiologiesmentioning
confidence: 99%
“…Importantly, cardiac myocytes express TNF receptors TNFR1 (TNFRp55) and TNFR2 (TNFRp75), implicating the possible importance of enhance TNF-in the myocardium. Histological analysis revealed that myocardial necrosis and cellular infiltration are more prominent in TNF--positive cases further supporting the notion that the expression of TNF-significantly contributes to the pathogenesis of viral myocarditis and including the severity of cardiac dysfunction (Calabrese et al 2004). Chemokines act as chemotactic mediators in leukocyte trafficking to sites of infection (Groom et al 2011).…”
Section: Wwwintechopencommentioning
confidence: 51%